Our friends the enemies : the occupation of France after Napoleon - Haynes, Christine, 1970- (Harvard University Press, 2018)
Contrary to popular understanding, the Napoleonic Wars did not end in 1815 at Waterloo. The battle was only the beginning of a long and complex transition to peace. To end this first "total" war, the powers allied against Napoleon developed a new approach to peace-making: a military occupation designed not to conquer territory, but rather to guarantee that the defeated nation reconstruct itself and repay the damages it had caused. Our Friends the Enemies provides the first comprehensive history of the post-Napoleonic "occupation of guarantee." From 1815 to 1818, a multinational occupation force of 150,000 men was stationed in seven departments along the northeastern frontier, at the expense of the French government. Recounting the experience of both occupiers and occupied, the author shows that while the occupation inevitably involved some violence, it also promoted considerable exchange and reconciliation between the French and their former enemies. Although its significance has long been overlooked, the post-Napoleonic occupation of guarantee foreshadowed later efforts at postwar reconstruction, including the Allied occupations of Germany and Japan after World War II.--